Languages, gestures and movement as evasion strategies used by Dato' Seri Najib in news interview - Wan Mustaffa, Wan Muslihah; Abdullah, Nur Nabilah (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2019)
News interview is regarded as a form of institutional talk where the interaction process between the participants differs from an ordinary conversation in which the course of interaction in news interviews is an exchange of question-and-answer (Clayman & Heritage, 2002). This paper aims to explore evasion practices used by Dato’ Seri Najib Razak in an exclusive interview episode ‘101 East’ broadcasted live by Al Jazeera Channel on 26th October 2018. The data was collected from the online YouTube videos in which the participants in the 101 East were between the host interviewer, Mary Jolley, and the guest interviewee, Dato’ Seri Najib Razak. Using conversation analysis approach, this study analyzed how the interviewee evaded from answering controversial questions in the interview. The findings suggest that language, gestures and movement were used by the interviewee as evasion strategies to avoid from answering questions and to terminate topics in the interview. The organization of gestures and movement used by the interviewee as evasion strategies in this study were forewarning, interruption, final thanks and body movement.